Hierarchically‐Porous Carbon Derived from a Large‐Scale Iron‐based Organometallic Complex for Versatile Energy Storage. Issue 12 (24th May 2016) - Fan, Chao‐Ying; Li, Huan‐Huan; Wang, Hai‐Feng; Sun, Hai‐Zhu; Wu, Xing‐Long; Zhang, Jing‐Ping
Abstract: Inspired by the preparation of the hierarchically‐porous carbon (HPC) derived from metal organic frameworks (MOFs) for energy storage, in this work, a simple iron‐based metal– organic complex (MOC), which was simpler and cheaper compared with the MOF, was selected to achieve versatile energy storage. The intertwined 1 D nanospindles and enriched‐oxygen doping of the HPC was obtained after one‐step carbonization of the MOC. When employed in lithium‐ion batteries, the HPC exhibited reversible capacity of 778 mA h g −1 after 60 cycles at 50 mA g −1 . Moreover, the HPC maintained a capacity of 188 mA h g −1 after 400 cycles at 100 mA g −1 as the anode material in a sodium‐ion battery. In addition, the HPC served as the cathode matrix for evaluation of a lithium–sulfur battery. The general preparation process of the HPC is commercial, which is responsible for the large‐scale production for its practical application. Abstract : Complex applications : A large‐scale iron‐based organometallic complex is selected as a precursor to prepare hierarchically‐porous 1 D carbon (HPC) nanospindles enriched with oxygen heteroatoms through one‐step carbonization. The HPC exhibits versatile application for advanced energy storage and the decent electrochemical performance is acquired for each application.